River Incision in Relation to Post-Glacial Events in the Humber River Basin, Ontario - Phillips, Roger; Robert, André (Géographie physique et Quaternaire, 2005)
AbstractRiver valleys in the Humber River drainage basin have derived most of their morphology from processes occurring over the last 13 000 14C BP. Some of the valley reaches possess very distinct characteristics in terms of plan-view morphology, such as valley meandering and loop features along the valley sides. In this study, the valley morphology and stratigraphy of the upper Humber River basin are examined in order to assess the character of post-glacial valley evolution. Existing knowledge of late Wisconsinan and Holocene events has been considered to place this valley evolution into a regional context. Radiocarbon dating and digital elevation models suggest that the majority of valley incision occurred during or soon after regional deglaciation. Looping valley features and terrace patterns indicate that most valley morphology can be attributed to larger ancestral rivers. Although direct melt-water contributions are expected due to deglaciation, it is suggested that other processes due to the climatic and hydrogeologic effects of fluctuating proglacial lake levels also played a role.